Conceptual-Practical Disparities in Inclusive Education: An Analysis of School Principals’ and Teachers’ Competencies in Indonesia - Muhammad Rizki; Wagino (ASANKA : Journal of Social Science and Education, 2026)
This study aims to analyze the gap between conceptual understanding and practice of inclusive education at the managerial and pedagogical levels. The study used a mixed-methods approach with a sequential explanatory design. Quantitative data were collected via questionnaires from 56 school principals and supervisors in Tuban Regency and from 99 special education teachers across various regions in Indonesia. Data were analyzed using descriptive statistics, while open-ended responses were analyzed through thematic analysis. The results indicate that school principals and supervisors have a relatively high understanding of the basic values of inclusive education, particularly regarding children's rights to an adequate education and the importance of school support. However, this understanding has not been fully translated into institutional practice, particularly in facilities, adaptive learning resources, the use of assistive devices, and technical capabilities for identifying specific learning difficulties. At the teacher level, key challenges include limited ongoing training, school infrastructure, learning resources, and support for the educational ecosystem. These findings confirm that the gap in inclusive education is not only individual but also systemic. The implications of this study indicate the need to strengthen professional competencies, provide realistic institutional support, and collaborate across stakeholders to bridge the gap between the concept and practice of inclusive education in Indonesia.